Evaluating the Sunnah through the Qur’anic Criterion: A Critical Analysis of Taha Jabir al-Alwani’s Methodology - Ganai, Zafer Ahmad; Nabi, Nasir (Journal of Modern Islamic Studies and Civilization, 2026)
This paper presents a critical examination of Taha Jabir al-Alwani’s methodological approach to redefining the relationship between the Qur’an and the Sunnah. Building on his seminal work Reviving the Balance: The Authority of the Qur’an and the Status of the Sunnah, the study investigates al-Alwani’s principal argument that the Qur’an should serve as the supreme criterion (mīzān) for evaluating the authenticity, interpretation, and practical application of the Sunnah. Al-Alwani proposes a classification of Prophetic traditions based on their degree of conformity with the Qur’an, assigning distinct levels of authority in accordance with this alignment. In his view, the Sunnah derives its authority and interpretive significance from the Qur’an, functioning as a practical exposition of its teachings rather than as an independent and autonomous source of revelation. The study focuses on three core methodological dimensions that define al-Alwani’s approach: (1) Methodological Difficulties in Dealing with the Sunnah, which address the inconsistency and overreliance on transmitted reports without adequate Qur’anic contextualization; (2) Difficulties Relating to the Legacy Left by Usulī Scholars, which critiques how classical juristic frameworks contributed to the epistemological separation between the Qur’an and the Sunnah; and (3) Isnad Methodology in Isolation, which challenges the traditional emphasis on the chain of transmission without sufficient textual (matn) scrutiny in light of Qur’anic principles. However, al-Alwani’s perspective is critically examined against the views of the jumhūr (majority) of hadith scholars, who hold a different stance on the legitimate value of the Sunnah. Through this comparative and analytical lens, the paper evaluates al-Alwani’s efforts to construct a Qur’an-centered hermeneutical framework that seeks to harmonize authenticity, ethical intent, and contextual relevance. Ultimately, the study situates his approach within the broader landscape of modern Islamic reformist thought, underscoring his contribution to reaffirming the Qur’an’s central position in the interpretation of the Sunnah and in the renewal of Islamic jurisprudence.